Pengembangan Media Game Edukasi untuk Meningkatkan Kemampuan Numerasi Siswa Kelas IV Sekolah Dasar - Karseno Karseno (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
Courageous learning during the pandemic caused low student mathematics learning outcomes due to the teacher's difficulties in explaining the material and the lack of learning media. This development research aims to produce educational game media on the topic of integers for class VI Elementary School that are valid and practical. This study uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection methods used were tests and questionnaires involving experts, teachers and students. A limited trial was carried out boldly on 21 grade VI students at SD Negeri 2 Banjar Anyar to find out the practicality of educational games and their numeracy skills. The results of the validity test of this educational game obtained a score of 4.85 for material experts and 4.88 for media experts, which means very good. For practicality, a score of 4.5 is obtained with very good criteria. Students' numeracy skills increased from 38% of students completing to 81%. The results of the questionnaire showed that 95% of students enjoyed learning using educational games. It can be concluded that this educational game can be used as a medium for learning mathematics on the topic of integers for grade VI Elementary School and can increase students' motivation and numeracy skills.